Geomagnetics for Aeronautical Safety A Case Study in and around the Balkans - Rasson, Jean L.; Delipetrov, Todor; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Flying safely in aircraft implies the use of navigation instruments. Among them, the magnetic compass is still a first choice for orientation and it is compulsory in all aircraft. In our increasingly sophisticated but fragile world of global navigation systems and gyroscopic sensors, the compass is especially useful as a back-up: it is highly reliable and likely to survive in harsh electromagnetic aggressions or when all power supplies fail. This book examines in detail how the science of geomagnetism is able to promote correct use of the magnetic compass for navigation. A selected group of specialists met in Ohrid, Macedonia to expose their approaches to the question. Using techniques from Geology, Instrument science, Magnetism, Chaos theory and Potential Fields applied to the Balkan region and surroundings, they put together a roadmap to fully tackle the issue of measurement, analysis, mapping and forecasting the magnetic declination in support of aeronautical safety.
INTRODUCTORY ADDRESS -- TO THE ADVANCED RESEARCH WORKSHOP: (3z(BNEW MAGNETIC FIELD DATA IN THE FORMER YUGOSLAV REPUBLIC OF MACEDONIA FOR ENHANCED FLYING AND AIRPORT SAFETY(3y (B-- GEOMAGNETIC FIELD OF THE REPUBLIC OF MACEDONIA -- GEOMAGNETIC FIELD MEASUREMENTS AT MAGNETIC REPEAT STATIONS IN FORMER YUGOSLAVIA -- FIELD AND OBSERVATORY GEOMAGNETIC MEASUREMENTS IN BULGARIA -- ON THE MODELLING OF A GEOMAGNETIC REFERENCE FIELD FOR THE BALKAN REGION -- REPEAT SURVEYS OF MACEDONIA -- NATURE OF EARTH$1 (BS MAGNETIC FIELD AND ITS APPLICATION FOR COMMERCIAL FLIGHT NAVIGATION -- GEOMAGNETIC OBSERVATIONS IN TURKEY -- CROATIAN GEOMAGNETIC REPEAT STATIONS NETWORK -- GEOMAGNETIC INSTRUMENTATION FOR REPEAT STATION SURVEY -- PROBLEMS OF SUPPLY IN DI-FLUX INSTRUMENTS -- DEVELOPMENT OF AN AUTOMATIC DECLINATIONINCLINATION MAGNETOMETER -- NEW MAGNETIC MATERIALS -- PROGRESS AND LIMITATIONS IN MAGNETIC FIELD MEASUREMENTS -- GEOMAGNETIC MEASUREMENTS FOR AERONAUTICS -- MEASUREMENTS OF MAGNETIC DECLINATION AT THE AIRPORTS IN BULGARIA -- GEOMAGNETIC MEASUREMENTS AND MAPPING FOR AERONAUTICS IN GERMANY -- AIRPORT GEOMAGNETIC SURVEYS IN THE UNITED STATES -- MAGNETIC REPEAT STATION NETWORK IN ITALY AND MAGNETIC MEASUREMENTS AT HELIPORTS AND AIRPORTS -- AIRPORT CONDITIONS IN MACEDONIA: SEISMIC RISKS -- NONLINEAR TECHNIQUES FOR SHORT TERM PREDICTION OF THE GEOMAGNETIC FIELD AND ITS SECULAR VARIATION -- SPHERICAL CAP HARMONIC ANALYSIS OF THE GEOMAGNETIC FIELD WITH APPLICATION FOR AERONAUTICAL MAPPING -- ACTIVITIES COMPLETED TOWARD ESTABLISHING A GEOMAGNETIC OBSERVATORY IN THE REPUBLIC OF MACEDONIA -- ANALYSIS OF GEOMAGNETIC FIELD DATA FROM MEASUREMENTS DURING 2003 IN MACEDONIA -- UNDERSTANDING THE GEOMAGNETIC FIELD: A PRECONDITION FOR BETTER LIVING.s
Keywords: Physics; Geographical information systems; Mathematical analysis; Analysis (Mathematics).; Potential theory (Mathematics).; Physical measurements; Measurement; Electronics; Microelectronics; Physics; Physics, general; Analysis; Geographical Information Systems/Cartography.; Potential Theory; Electronics and Microelectronics, Instrumentation; Measurement Science and Instrumentation; Electronic books